The Effect of Product Knowledge and Risk Perception on Consumers’ Online Word-of -Mouth Search Behavior for the Bio-Agricultural Products–in the Case of Ganoderma Dietary Supplements - Chang, Yung-Chia; Huang, Li-Chun (International Journal of Environment, Agriculture and Biotechnology, 2019)
Many consumers have adopted the food of dietary supplements. However, since the threshold of professional knowledge for dietary supplements is usually high, most of the consumers do not possess sufficient knowledge for making an appropriate purchase decisions as they concern buying the products of dietary supplements. As a result, many consumers rely on word-of-mouth as they need to make purchase decisions on buying dietary supplements. It causes health risk to consumers since the word-of-mouth may be wrong and thus to make consumers take wrong dietary supplements. To address this deficiency, this study explores how consumers’ knowledge for dietary supplements and risk perceptions influence their search behavior for word-of-mouth in the purchase of dietary supplements. With a two-stage cluster sampling strategy, 370 questionnaires were distributed to thecustomers of retail stores for selling Ganoderma dietary supplements, while 314 questionnaires were valid for statistical analysis. With the analysis of linear structural equation modeling, the causal structural relation among consumers’ product knowledge, risk perception and word-of-mouth search behavior was examined. According to the statistical results, consumers’ subjective product knowledge has greater overall impacts on the degree of word-of-mouth search behavior, compared with consumers’ objective product knowledge. Namely, if consumers have more subjective knowledge for products, they are less likely to rely on word-of-mouth for the purchase of dietary supplements. For promoting the concept of food safety to consumers, consumers should be prepared with more correct product knowledge, in order to develop trust in self product knowledge in the publicity of safe consumption of dietary supplements, and reduce their dependence on the reputation of the dietary supplements without clear sources.